2019
DOI: 10.1002/uog.20203
|View full text |Cite
|
Sign up to set email alerts
|

Management of monoamniotic twins: the question is not ‘where?’, but ‘how?’

Abstract: https://obgyn.onlinelibrary.wiley.com/doi/abs/10.1002/uog.19179

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…As for the risk of perinatal death, this can be reduced by aiming to deliver at around 32 weeks' gestation 37,38 . The outcome may not be different if monitoring after 26 weeks' gestation is carried out on an outpatient basis compared to hospitalization [39][40][41] .…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…As for the risk of perinatal death, this can be reduced by aiming to deliver at around 32 weeks' gestation 37,38 . The outcome may not be different if monitoring after 26 weeks' gestation is carried out on an outpatient basis compared to hospitalization [39][40][41] .…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…The results suggested that perinatal mortality rate was lower in the inpatient group, but the results were inconclusive. However, this has been contradicted by others [18]. The hemodynamic instability between the two fetuses is a causal factor behind sudden fetal demise in these pregnancies.…”
Section: Discussionmentioning
confidence: 90%
“…The appropriate management of monoamniotic twins is still unclear and varies among clinicians [ 3 ]. There appears to be agreement that prior to viability, early confirmation of chorionicity and amnionicity, as well as identification of fetal anomalies should be performed [ 4 ].…”
Section: Discussionmentioning
confidence: 99%